Combined detection and subclass characteristics analysis of CTCs and CTECs by SE-iFISH in ovarian cancer - Cheng, Hongyan; Wang, Shang; Luan, Wenqing; Ye, Xue; Dou, Sha; Tang, Zhijian; Zhu, Honglan; Ping Lin, Peter; Li, Yi; Cui, Heng; Chang, Xiaohong (Chinese journal of cancer research, 2021)
Hematogenous metastasis is essential for the progression of ovarian cancer (OC), and circulating tumor cells (CTCs) are part of the metastatic cascade. However, the detection rate of CTC is low due to the use of less sensitive detection methods. Therefore, this study aimed to detect CTCs and circulating tumorigenic endothelial cells (CTECs) in patients with OC using subtraction enrichment and immunostaining and fluorescence hybridization (SE-iFISH). We enrolled a total of 56 subjects, including 20 OC patients and 36 ovarian benign tumor patients. CTCs and CTECs were captured by subtraction enrichment (SE) and counted and classified according to immunofluorescence staining of tumor markers (TMs) carbohydrate antigen 125 (CA125) and human epididymis protein 4 (HE4) combined with fluorescence hybridization (iFISH) of chromosome 8 (Chr8) aneuploidy. The diagnostic value and subtype characteristics of CTCs and CTECs were investigated. The detection rate of CTCs by SE-iFISH was high. Compared with CA125 and HE4, Chr8 aneuploidy was the major identification feature of CTC. CTC counts in OC were statistically higher than those in benign groups. CTC and CTEC with ≥pentaploidy were detected in both groups, illustrating the poor diagnostic value of CTC or CTEC. Distributions of triploid and tetraploid CTC subtypes were significantly different, and combined detection of triploid and tetraploid CTCs showed the best diagnostic value. In contrast, the distribution of CTECs in the OC and benign groups had no statistically significant difference. Small CTCs accounted for over 1/3 of the total CTC count. We also found that small CTCs and CTECs primarily comprised triploid cells, while large CTCs and CTECs mainly comprised pentaploidy and beyond. The application of SE-iFISH offered a more comprehensive understanding of heterogeneous CTCs and CTECs in OC. Analysis of subclass characteristics of the CTCs and CTECs according to Chr8 aneuploidy and cell size may broaden their potential clinical utility and deepen mechanistic studies in OC.